A spectroscopic study on the satellite vibronic band in phosphorescent Pt-complexes with high colour purity. Issue 48 (1st December 2017) - Son, Mi Rang; Cho, Yang-Jin; Son, Ho-Jin; Cho, Dae Won; Kang, Sang Ook
Abstract : The major origin of the satellite vibration band in emission spectra is the stretching of the terminal groups, which can be confirmed by IR and Raman spectroscopic techniques. Abstract : To understand the relationship between the narrowing of an emission band and structural changes, we synthesised tetradentate Pt-complexes.Pt-1 has two directly connected carbazole (Cz) moieties, Pt-2 has two additional methyl groups toPt-1, andPt-3 has one Cz moiety. The absorption and emission spectra ofPt-2 were identical to those ofPt-1 .Pt-3 's emission was observed at a shorter wavelength compared to the others. We achieved phosphorescence with high colour purity by introducing a tetradentate ligand. All the Pt-complexes showed a vibronic structure in the emission spectra measured at 77 and 300 K. The 0–0 vibronic band of the Pt-complexes is quite intense compared to the 0–1 vibronic band, which may be due to less structural change of the fused tetradentate ligand in the excited state relative to the ground state. The spacing of the 0–0 and 1–0 vibronic bands is 1487 and 1323 cm −1, respectively. To understand the origin of the satellite vibronic bands, we carried out vibrational spectroscopic (IR and Raman) measurements and theoretical calculations to analyse the infrared spectrum. In addition, we carried out a transient Raman experiment to obtain the vibronic information of an excitedPt-1 . The vibronic spacing in the emission was caused by the displacement of the potential energy curve in the excited state. The highest occupied molecular orbital is populated with a Cz moiety and the lowest unoccupied molecular orbital is localized at the terminal pyridine moiety. For the triplet state, however, the highest singly occupied molecular orbital is delocalized on the pyrazole or imidazole moiety, as well as the pyridine moiety. These groups are located at the terminal site of the ligand, and are less rigidified and more flexible. Therefore, the major origin of the satellite vibration band in emission spectra is the stretching of the terminal groups.